The European Community of Law and the Communities of Case-law: Understanding legal concepts and processes through the lens of community detection algorithms - Urška Šadl; Lucía López Zurita; Sebastiano Piccolo (European Law Open)
Community detection is a set of algorithms developed in network science to find meaningful sub-groups within larger groups. This article (1) outlines and evaluates the method and (2) shows how it can enrich ongoing debates about European integration. To this end, it uses the example of the approximation of laws, an enduring topic in European legal studies.